Effect of Preoperative Serum Lactate Dehydrogenase-to-Albumin Ratio on the Survival of Oral Cancer: A Retrospective Study - Wang X; Ji X (Dove Medical Press, 2024)
Xuming Wang, Xiaoli Ji Department of Stomatology, The Affiliated Huaian No.1 People's Hospital of Nanjing Medical University, Huaian, Jiangsu, People's Republic of ChinaCorrespondence: Xiaoli Ji, Email jixiaoli214@163.comBackground: Several studies have investigated the relationship between serum lactate dehydrogenase-to-albumin ratio (LAR) and the prognosis of cancers. However, no studies have explored the association between serum LAR and the survival of oral cancer (OC). This study was aimed to determine the association of serum LAR with the overall survival (OS) of OC.Methods: One hundred and ninety patients with OC were included in this study between January 2018 and December 2019. Log rank test and Kaplan-Meier method were used to compare the survival rate of OC between the low LAR group and the high LAR group. The association between serum LAR and the survival of OC patients was determined via univariate and multivariate Cox regression analyses.Results: Kaplan-Meier analysis and Log rank test indicated that the OS rate in low LAR group was significantly higher than that in high LAR group (P < 0.05). Univariate cox analysis showed that TNM III-IV stage, serum LDH > 162 U/L, and serum LAR > 3.79 were significantly associated with the OS of OC patients. Multivariate Cox analysis suggested that the TNM III-IV stage (HR, 2.317; 95% CI, 1.423- 3.774, P = 0.001) and serum LAR > 3.79 (HR, 5.138; 95% CI, 2.245- 11.756, P = 0.000) were independently related with poor OS of OC patients.Conclusion: High serum LAR (> 3.79) is an independent predictor of adverse prognosis in OC patients. LAR could be used as a promising marker for predicting the OS of OC patients.Keywords: oral cancer, lactate dehydrogenase to albumin ratio, prognosis, marker